'The social fabric of cities': a tripartite approach to cities as systems of interaction. Issue 2 (4th May 2017) - Netto, Vinicius M.
ABSTRACT: This paper introduces the main ideas of an integrated approach intended to address three vital yet relatively little explored dimensions in the social and material shaping of cities. First, it looks into 'cities as systems of encounters' in time and space – or how we find ourselves co-present with those like us or those different from us in public and private places. Second, it introduces a view to 'cities as systems of communication' – or how cities become contexts that help us to produce linguistic exchanges and create massive action systems from seemingly trivial situations. Third, it looks into 'cities as systems of material interaction' – or why we shape and fold space into urban space in order to express interactions in complex conditions of interdependence. Finally, the paper discusses substantive and epistemological issues regarding the improbable connections between the elusiveness of actions and the perennial tangibility of their spatialities.